Age-related decrease of meiotic cohesins in human oocytes. - Makiko Tsutsumi (Public Library of Science (PLoS), 2014)
Aneuploidy in fetal chromosomes is one of the causes of pregnancy loss and of congenital birth defects. It is known that the frequency of oocyte aneuploidy increases with the human maternal age. Recent data have highlighted the contribution of cohesin complexes in the correct segregation of meiotic chromosomes. In mammalian oocytes, cohesion is established during the fetal stages and meiosis-specific cohesin subunits are not replenished after birth, raising the possibility that the long meiotic arrest of oocytes facilitates a deterioration of cohesion that leads to age-related increases in aneuploidy. We here examined the cohesin levels in dictyate oocytes from different age groups of humans and mice by immunofluorescence analyses of ovarian sections. The meiosis-specific cohesin subunits, REC8 and SMC1B, were found to be decreased in women aged 40 and over compared with those aged around 20 years (P<0.01). Age-related decreases in meiotic cohesins were also evident in mice. Interestingly, SMC1A, the mitotic counterpart of SMC1B, was substantially detectable in human oocytes, but little expressed in mice. Further, the amount of mitotic cohesins of mice slightly increased with age. These results suggest that, mitotic and meiotic cohesins may operate in a coordinated way to maintain cohesions over a sustained period in humans and that age-related decreases in meiotic cohesin subunits impair sister chromatid cohesion leading to increased segregation errors.